Vancomycin microspheres reduce postoperative spine infection in an in vivo rabbit model. Issue 1 (December 2016) - Liu, Gang; Chen, Si; Fang, Jun; Xu, Baoshan; Li, Shuang; Hao, Yonghong; Al-Dhabi, Naif; Deng, Shucai; Duraipandiyan, Veeramuthu
Abstract Background Surgical site infections are common and devastating complications after implants related surgeries.Staphylococcus aureus contamination is a leading cause of surgical site infections. This study aims at assessing the effect of vancomycin microspheres on reducingStaphylococcus aureus infection in an in vivo rabbit model. Methods Sixty surgical sites of 20 New Zealand White rabbits underwent spinal implant were randomly divided to three groups: the control group, the vancomycin group and vancomycin microspheres group. The surgical sites were incubated with 100 μl 1 × 107  CFU S. aureus ATCC 25923. Prior to closure, vancomycin and vancomycin microspheres were placed into the wounds of the rabbits in the vancomycin group and the vancomycin microspheres group, respectively. The rabbits were killed on postoperative day 7. Standard quantification techniques were used to analyze biomaterial centered and soft tissue bacterial growth. The bacteria were further confirmed by PCR with primers from the thermostable nuclease gene ofS. aureus. Results All the rabbits survived the surgery and no postoperative wound complications or systemic illness occurred. Results showed that the bacterial cultures were 76.9, 30.8, and 15.4% in the control group, vancomycin group, and vancomycin microspheres group. Vancomycin microspheres treatments significantly decreased the infection rate compared to the control group (p  < 0.05). Conclusion Vancomycin microspheres combined with preoperative ceftriaxone is effective to reduce postoperativeS. aureus infection compared with the control group.